Public Health Effects of Polycyclic Aromatic Hydrocarbons Exposure Through Air, Water, Soil, and Food in Ghana: Possible Economic Burden - Prosper Manu Abdulai; Onyinyechi Bede-Ojimadu; Amarachi Paschaline Onyena; Chiara Frazzoli; Naomi A. Mogborukor; Osazuwa Clinton Ekhator; Godswill J. Udom; Eudora Nwanaforo; Orish Ebere Orisakwe (Environmental Health Insights)
Exposure to polycyclic aromatic hydrocarbons (PAHs) is a major threat to public health and economic stability, particularly in Sub-Saharan African countries such as Ghana. However, limited consolidated evidence exists on the extent of exposure, associated health outcomes, and economic impacts. This systematic review aimed to summarize available studies on health effects of PAH exposure in Ghana and assess potential economic implications. A comprehensive search of PubMed, Scopus, Google Scholar, and African Journals Online was conducted for studies published between January 2014 and January 2025. Sixteen studies met the eligibility criteria. Considerable heterogeneity was observed regarding study designs, target populations, matrices assessed, and PAH analytes measured. Most studies were ecological, limiting comparability and economic estimation. Nonetheless, findings indicate significant exposure to PAHs through environmental (soil, street dust, particulate matter) and occupational (fish smoking, urban living) sources. Urinary PAH metabolite levels among exposed groups were substantially elevated, and over 70% of studies reported carcinogenic risk indices exceeding WHO and USEPA thresholds of 1 × 10⁻⁶. Health effects such as persistent cough, chronic headaches, tachycardia, and dyspnea were reported. Although no Ghanaian study directly evaluated the economic burden, the evidence suggests increased healthcare costs, productivity losses, and environmental remediation expenses. This review identifies critical gaps, including the need for personal exposure measurements, longitudinal health assessments, and economic evaluations. Addressing these gaps is essential for informed policy development and resource allocation to reduce the health and economic impacts of PAH pollution in Ghana.